Relevant norms of Roman law in Russian civil legislation - Mikhail Y. Ushakov; Oleg A. Mekka (Russian Studies in Law and Politics, 2025)
Background. The article examines the impact of Roman Law principles on contemporary Russian civil legislation. The authors analyze key legal institutions, such as principle of bona fides, easements (servitutes), contractural obligations (pacta sunt servanda), and inheritance law, tracing their continuity and adaption with the Russian legal framework. Special attention is given to the relevance of these institutions in the context of economic digitalization and the development of market relations.